Perancangan Game FPS (First Person Shooter) Police Personal Training - Robert T. Singkoh; Arie S.M. Lumenta; Virginia Tulenan (Universitas Sam Ratulangi, 2016)
Abstract– The purpose and benefits of the preparation of this paper, which is to do the design and introduction of the training of the police firing training into the game in order to provide entertainment and learning to users. In addition to giving lessons to the manufacture of this paper is expected to be a springboard for the users to be able to express their work to make the game either for entertainment purposes or for research. Police Personal Shooter game modeling with Blender application and use the Unity as game engine.Blender is a open source modeling application that used to create animations and modeling. otherwise Unity 5 is a game engine application that is often used to make game.this Game Police Personal Shooter includes a simple and easy to complete .There are two scenes in this game. Scene one is shooting target and scene two to destroy terrorist image. Players who are candidates for the police enough to get a certain score by shooting the target and destroy terrorist image to get score and finish the game. Â Keywords: Blender, Game Engine, Open Source, Personal Police Shooter, Unity 5Â abstrak– Adapun tujuan dan manfaat dari penyusunan skripsi ini, yaitu untuk melakukan perancangan dan pengenalan mengenai pelatihan menembak yang dilakukan polisi ke dalam game agar dapat memberikan hiburan dan pembelajaran kepada pengguna. Di samping memberikan pembelajaran kepada pengguna pembuatan skripsi ini diharapkan dapat menjadi batu loncatan untuk para pengguna untuk dapat mengekspresikan karya mereka dengan membuat game entah untuk tujuan hiburan maupun untuk penelitian. Game Police Personal Shooter ini dimodeling dengan aplikasi Blender dan menggunakan Unity 5 sebagai game engine.Blender merupakan aplikasi modeling open source yang banyak digunakan untuk membuat animasi dan modeling.selain itu Unity 5 merupakan aplikasi game engine yang sering digunakan untuk membuat game.Game Police Personal Shooter termasuk sederhana dan mudah untuk diselesaikan.Terdapat 2 scene dalam game ini. Scene 1 yaitu menembak target sasaran dan scene 2 menghancurkan gambar teroris. Pemain yang merupakan calon polisi cukup mendapatkan score tertentu dengan menembak target sasaran dan menghancurkan gambar teroris untuk mendapatkan score dan menyelesaikan permainan. Kata Kunci : Blender, Game Engine, Open Source, Personal Police Shooter, Unity 5